Studi Kapasitas Dan Tingkat Pelayanan Simpang Asrama Haji : Studi Kasus Jalan Perintis Kemerdekaan Km. 18 Sudiang, Kota Makassar - Komang Widi Widiana; Abd. Rahim Nurdin; Tamrin Mallawangeng (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
In this paper, calculations will be made to evaluate the vehicle capacity and performance of the street corners on the Jl. Perintis Kemerdekaan Km. 18,  Jl. poros Maros – Makassar and Goa Ria street and how big the level of service is at the Asrama Haji street corners. Jl. Perintis Kemerdekaan Km. 18,  Jl. poros Maros – Makassar and Jl. Goa Ria. Processing and analyzing data using MKJI 1997. The results of the research on the Asrama Haji intersection from the calculation concluded that the performance condition of the intersection is at level F, where, Jalan Poros Maros - Makassar has the highest traffic volume, 4104 pcu/hour, total flow point (QTOT) = 8588 pcu/hour capacity value ( C) = 3041 pcu/hour and degree of saturation (DS) = 1.35. and has a service level of F where the value of the degree of saturation is >1.00. For Jalan Poros Makassar – Maros, it is 2915 pcu/hour, the capacity value (C) = 2920 pcu/hour and the degree of saturation (DS) = 1.00. and has a service level E where the value of the degree of saturation ranges from 0.85 to 1.00. For Jl. Goa Ria is 1568 pcu/hour, capacity value (C) = 3101 pcu/hour and degree of saturation (DS) = 0,51. and has a service level of C where the degree of saturation is 0.45 – 0.74